PRODUKSI DAN KONSUMSI OKSIGEN ZONA ATAS DAN BAWAH SECCHI DISK DI WADUK BENANGA SAMARINDA - Anggara Sakti Pribadi; Muhammad R. Syahrir; Ghitarina Ghitarina (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
The high sedimentation and erosion in reservoirs in Indonesia have been the main factors causing the decrease in reservoir capacity. High sedimentation is the main factor causing the decline in the carrying capacity of the reservoir ecosystem. This research was conducted to determine the production of dissolved oxygen and respiration in the upper and lower zones of the sechi disk in the Benanga Reservoir. As data on dissolved oxygen production and respiration in the upper and lower zones of the secchi disk. This study uses a dark and light bottle storage method to see the difference between the upper and lower zones of the waters so as to get the production and oxygen consumption. Dissolved oxygen production and consumption studies (dark and light bottles) used a 4-hour incubation. The results show that the dissolved oxygen consumption in the upper zone is 2.07 mg/L and the lower zone is 1.90 mg/L, gross primary productivity (GPP) in the upper zone is 4.95 mg/L and the lower zone is 4.32 mg/L, and the net primary productivity (NPP) is in the upper zone. 2.88 mg/L and lower zone 2.42 mg/L.